Navigating Tuberous Sclerosis in a 41-Year-Old Patient: Clinical Insights and Management - Yanamadala, Pavan Kumar; Vemana, Hema Ratna Sai Lakshmi; Sana, Praveen; Allavarapu, Manogna; Chikkala, Bhagya Aruna (Indian Journal of Pharmacy Practice)
Tuberous sclerosis complex is a rare genetic disorder that is characterized by the presence of non-cancerous tumors in different organs, primarily affecting the brain, skin, kidneys, heart, and lungs. This condition is caused by mutations in either the TSC1 or TSC2 genes, which disrupt the mTOR pathway. The clinical manifestations of TSC can vary greatly, ranging from mild skin abnormalities to more severe neurological problems such as epilepsy, cognitive impairment, and autism spectrum disorders. Tumors and cystic lesions of the kidneys can be the associated abnormalities of the renal tract. While in most cases, they can be asymptomatic, adverse effects on renal function have also been reported. The case study details a 41-year-old woman who received a belated diagnosis of TSC. She had a history of seizures over the past 26 years, with a physical examination revealing classic TSC features such as facial angiofibroma, enamel pits, and periungual fibromas. The patient also had a background of learning difficulties. She was diagnosed with advanced renal failure which was picked up when she presented with pedal oedema. She ended up on dialysis a few months following the presentation. Treatment for TSC typically targets specific symptoms, with antiepileptic medications prescribed for seizures and surgical interventions for sizable tumors. Regular monitoring is essential to detect potential complications early on. The case emphasizes the significance of prompt diagnosis and comprehensive care in TSC to enhance patient outcomes and well-being. Given the disease's diverse nature, regular check-ups and tailored treatment strategies are vital for effective management.
Keywords: Angiofibromas; Enamel pits; Intellectual disability; Multiple hamartomas; Seizures; Tuberous Sclerosis Complex